2022
DOI: 10.1109/access.2021.3138353
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Internet of Things From Blockchain to IOTA: A Survey

Abstract: Internet of Things (IoT) is the new paradigm to the scaling nature of things and their elements, interconnected, exchanging data over a network supported with nodes. The Ubiquitous use of tiny devices and embedded sensor frameworks has pushed IoT to the forefront of emerging technologies used in many applications like peer-to-peer networks, smart energy grids, home and building automation, vehicle to vehicle communication, and wearable computing devices. This massive growth and extensive use brought forth sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 117 publications
0
19
0
Order By: Relevance
“…Recurrent joint bleeding may be present in up to 25% of cases, and the diagnosis usually gets delayed until late childhood or adulthood. While in severe hemophilia, bleeding will present spontaneously and will appear early in life due to a lack of transmission of coagulation factors trans-placentally [5].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent joint bleeding may be present in up to 25% of cases, and the diagnosis usually gets delayed until late childhood or adulthood. While in severe hemophilia, bleeding will present spontaneously and will appear early in life due to a lack of transmission of coagulation factors trans-placentally [5].…”
Section: Discussionmentioning
confidence: 99%
“…To improve the transaction security, the communication between CSs and drone is secured by using different energy-efficient consensus mechanism of blockchain technology such as the Internet of things application (IOTA) [ 46 ]. IOTA is a consensus protocol in blockchain specially designed for low power Internet of things (IoT) networks and more detailed study can be found in [ 53 ].…”
Section: Drone Routing Algorithmsmentioning
confidence: 99%
“…Inside [27], their authors propose an alternative system approach while interacting IOTA with the Blockchain to reduce the transactional fees and power processing costs while peering at the ledger network. In a recent article, [107], an attempt to project the system evolution from Internet-of-Everything to IoT/Ledger is being performed, mainly from the application & applicability layer. The research article in [108] addresses the key security attacks as well as their security solutions that will help, according to the authors, establish stronger Blockchain systems.…”
Section: Iota Comprehensive Security Analysismentioning
confidence: 99%